Production, Post-Harvest and Marketing of Kaffir Lime (Citrus hystrix DC) In Tulungagung, Indonesia - Budiarto, Rahmat; Poerwanto, Roedhy; Santosa, Edi; Efendi, Darda; Agusta, Andria (Journal of Tropical Crop Science, 2019)
Kaffir lime (Citrus hystrix DC) is one of the Citrus species that is popular as food spices in Indonesia. This study was aimed at describing the production system, post-harvest handling, marketing and evaluating the product variation of kaffir lime cultivated in the Tulungagung district, East Java Province, Indonesia. Data was collected through a survey by interviewing kaffir lime farmers, distributors and customers in June 2018. Kaffir lime is cultivated by local farmers using traditional and conventional agriculture practices. The farmer used good quality seedlings as planting materials and applies animal manure or compost to the trees. Kaffir lime is grown on rain-fed land; fertilizers and pesticides are applied sparingly. The kaffir lime leaves could be harvested twice a year in different seasons. Better leaf quality can be obtained during the rainy seasons. The leaf production per tree is estimated at about 100 gram per plant per season. Post-harvest handling involved sorting, packing and marketing without any cooling treatment. The standard gate price of kaffir lime leaf in June 2019 was IDR 6,000-7,000, IDR 9,000-10,000 at the collector level, IDR 11,000-12,000 at wholesaler, and IDR 14,000-16,000 at small retailers. Leaves were distributed to traditional market in Tulungagung, neighbouring districts such as Kediri, Trenggalek and Blitar, and also to capital cities such Jakarta. The main product of kaffir lime is the fresh leaf for food seasoning and as a raw material to produce essential oil and dry leaf powder. The stems have been used for fuel in home industries. The fruits of kaffir lime are rarely found in the market and have great potentials for essential oil production and recently, a promising commodity for export.